Total eosinophil count as a biomarker for therapeutic effects of upadacitinib in atopic dermatitis over 48 weeks - Hagino, Teppei; Hamada, Risa; Yoshida, Mai; Fujimoto, Eita; Saeki, Hidehisa; Kanda, Naoko (Frontiers in Immunology, 2024)
Background: Atopic dermatitis (AD) is a chronic skin disease characterized by type 2-skewed immune responses, and significantly influenced by cytokines dependent on Janus kinases (JAKs). Upadacitinib, a JAK1 inhibitor, is effective for moderate-to-severe AD. This study aims to identify biomarkers that reflect long-term therapeutic effects of upadacitinib 15 mg or 30 mg. Methods: A retrospective study from August 2021 to July 2023 included 213 AD patients treated with upadacitinib 15 mg and 70 AD patients with 30 mg. We analyzed eczema area and severity index (EASI), peak pruritus-numerical rating scale (PP-NRS), serum immunoglobulin E (IgE), thymus and activation-regulated chemokine (TARC), lactate dehydrogenase (LDH), and total eosinophil count (TEC) at weeks 0, 4, 12, 24, 36, and 48 of treatment. Results: Both treatments with upadacitinib 15 mg and 30 mg significantly reduced EASI and PP-NRS scores over week 4 to 48 compared to baseline. Upadacitinib 15 mg or 30 mg treatment significantly decreased TEC compared to baseline through week 4 to 36 or week 4 to 48, respectively. The percent reduction of TEC correlated with those of EASI and PP-NRS through week 4 to 48 of treatment with upadacitinib 15 mg, or through week 12 to 48 with 30 mg, respectively. After adjusting for % reductions of other laboratory markers, the significance of correlations was preserved at weeks 36 and 48 of 15 mg treatment, while at weeks 4 and 36 of 30 mg treatment. Conclusion: The % reduction of TEC correlated with those of EASI and PP-NRS during upadacitinib treatment, indicating its potential as a biomarker reflecting treatment responses to upadacitinib in AD patients. However, the variability of significant correlation during treatment indicates that further inspection is needed for its usefulness in monitoring responses to upadacitinib treatment for AD.